Tipologi interaksi antara agama dan sains : Satu penilaian dan cadangan menurut perspektif Islami / Sh. Mohd Saifuddeen Sh. Mohd Salleh - Sh. Mohd Saifuddeen, Sh. Mohd Salleh (2012)
This research looks at the typologies of the interaction between religion and science. The focus of this research is on eight typologies of interaction between religion and science as proposed by thinkers in this field, namely Ian Barbour, Immanuel Kant, John Haught, Ted Peters, Margaret Osler, Wentzel van Huyysten, Stephen Jay Gould and Stephen Snobelen. These typologies are analysed and evaluated by looking at their suitability vis-à-vis the approaches suggested by Islamic thinkers in order to suggest the best typology for scientists and religious scholars to co-operate and interact in tackling the issues brought about by developments in science and technology. The findings of this research are: (i) Religion influences the development of science from the early days of mankind which brings about interactions which can be represented using typologies of interaction between religion and science; (ii) The typology of interaction proposed by Ian Barbour namely the conflict model, separation model, dialogue model and integration model is the most basic typology which is suitable to discuss the interaction between religion and science; (iii) The current interaction between Islam and science can best be represented using the separation model, while the ideal model for the interaction between Islam and science can be represented by the integration model; (iv) The best model for scientists and religious scholars to co-operate and interact in tackling the issues arising from the developments of science and technology is the dialogue model; and, (v) Muslim religious scholars can play a role in research and development of science and technology through continuous dialogue with scientists.///